Effectiveness of Problem-Solving Method in Developing Metacognitive Knowledge at Secondary School Level - Sajid, Ali Abbas; Rizwan, Dr. Sidra (VFAST Transactions on Education and Social Sciences, 2023)
This study was aimed to investigate the effectiveness of Problem-Solving Method (PSM)by using the acronym IDEAL in developing metacognitive knowledge at secondary level. The research was modeled in experiment-control groups design. A random selection of 120 students was taken from grade IX in the subject of General Science. These schools were randomly selected from the district on tehsil bases. 60 students from each school were divided into both control and experimental groups 30 students each randomly. The Revised Metacognitive Assessment Inventory (RMAI) was used to determine students’ metacognitive knowledge i.e., declarative, procedural and conditional knowledge. An Independent Samples t-test was used for analysis of the data. The lecture method was used in the control groups while the PSM was employed in the experimental group. The post-test results of the experimental and control groups on the bases of knowledge about cognition i.e., declarative, procedural and condition knowledge shows the difference was significant to reject the null hypothesis of H01 to H04 confirming a significant difference between the post-test of experimental groups taught through lecture and problem-solving method. The significant difference between the mean scores of both tests shows that students taught through the problem-solving method had prominent increase in metacognitive knowledge i.e., declarative procedural and conditional knowledge.